Management of failed carpal tunnel decompression - Arne Decramer; Carlos Heras-Palou; Maarten Van Nuffel; Tom Lattré; Ilse Degreef (EFORT Open Reviews)
Surgical decompression of carpal tunnel syndrome is usually successful, and failure is rare. Diagnosis of persistent or recurrent carpal tunnel syndrome is based on thorough anamnesis and clinical examination, defining underlying comorbidities, nerve conduction studies and distinguish recurrent, persistent or new complaints. Management of failed carpal tunnel release may require revision surgery, which includes redo release of the transversal carpal ligament, external neurolysis and flaps. A hypothenar fat pad flap or other local, regional or distant flaps may be added to a redo release of the carpal tunnel. Currently, convincing evidence to superiority of additional flap surgery is lacking. Postoperative care is evolving toward early motion rather than immobilization, with nerve gliding exercises to prevent adhesions and promote nerve recovery. Virtual reality was recently added to postoperative protocol options.